EXTRATO DE ALGAS NO CONTROLE DA PODRIDÃO PARDA E NA QUALIDADE PÓS-COLHEITA DE AMEIXAS - Oliari, Ires Cristina Ribeiro (2014)
The fruits of plum (Prunus salicina) have important features in nutraceutical sense, however, show high sensitivity to post-harvest losses with losses in nutritional characteristics. In this sense, the objective of this study was to evaluate the effect of extract of Ascophyllum nodosum algae and Ecklonia maxima in postharvest quality of plums `Irati` and `Reubennel` and in control of Monilinia fructicola, the causal agent of brown-rot. Experiments were conducted to verify the effect of five concentrations (0.0, 0.1, 0.2, 0.3 and 0.4 mL L?¹) of two commercial products containing seaweed extract (Algamare® and Booster®) the physico-chemical quality of plum fruit of both cultivars and control in vivo and in vitro M. fruticola the plums `Reubennel`. As standard treatment to control black pod used the fungicide Iprodione. The experimental design was completely randomized, with the analyzes performed at 15 and 30 days for `Irati` and `Reubennel`, respectively (two days shelf in natural conditions), making up five replications. The seaweed extracts studied the influence of the post-harvest quality plums and features of the fungus M. fructicola, especially when given higher doses. Variables ascorbic acid, total soluble solids, pH, soluble solids / titratable acidity of plum `Irati` and `Reubennel` were not influenced by both extracts. The extract of A. nodosum was efficient in delaying ripening plums, and the extract of E. maxima showed characteristics of acceleration of maturity under the conditions of this study. In vitro test doses had no significant effect on MIGS and sporulation of M. fructicola. However, the test was positive in vivo effect of the application of the extracts, with reduced AACPID of 41.03 and 26.90% for A. nodosum and E. maxima, respectively. A dose of 0.4 mL L?¹ of A. nodosum decreased, on average, 46.77% AUDPC compared with control equaling the iprodione treatment. It is concluded that organic and inorganic present in extracts of algae surveyed components induced physiological changes in the fruits of plums `Irati` and `Reubennel` changing post-harvest thereof, thus affecting shelf life, besides having beneficial effects regarding the control of the causal agent of brown-rot.